2006
DOI: 10.1007/s10047-005-0318-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of vitamin E-modified polysulfone membrane dialyzers

Abstract: Oxygen radicals have recently been attracting close attention because of their involvement in tissue damage and their close relationship to various clinical conditions. It has been suggested that hemodialysis increases oxidative stress, triggering the development of complications such as atherosclerosis and dialysis-related amyloidosis. We recently developed a dialyzer containing a highly functional polysulfone membrane on which vitamin E had been bonded (PS-ViE). The present study was undertaken to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 26 publications
3
31
0
1
Order By: Relevance
“…In the 1990s, a cellulosic hollow-fiber dialyzers coated with vitamin E on the blood surface was developed by the Terumo Corporation with triple goals of better filtration, an improvement in biocompatibility and antioxidant bioactivity. 31 Soon afterward, vitamin E-coated polysulfone dialyzer was developed, 32 which has such excellent properties as good biocompatibility, clearance, permeability, and is easy to process. In addition, a number of clinical studies and metaanalysis have demonstrated that the anti-inflammatory and antioxidative effects of these vitamin E modified dialyzers reflected by the decreasing of circulating biomarkers (e.g., CRP, IL-6 and oxLDL levels).…”
Section: Discussionmentioning
confidence: 99%
“…In the 1990s, a cellulosic hollow-fiber dialyzers coated with vitamin E on the blood surface was developed by the Terumo Corporation with triple goals of better filtration, an improvement in biocompatibility and antioxidant bioactivity. 31 Soon afterward, vitamin E-coated polysulfone dialyzer was developed, 32 which has such excellent properties as good biocompatibility, clearance, permeability, and is easy to process. In addition, a number of clinical studies and metaanalysis have demonstrated that the anti-inflammatory and antioxidative effects of these vitamin E modified dialyzers reflected by the decreasing of circulating biomarkers (e.g., CRP, IL-6 and oxLDL levels).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E, as α-tocopherol (α-TOC) (fig. 2), has been used to modify both cellulosic and polysulfone (PS) copolymers that are now available to produce hollow-fiber hemodialyzer membranes [recently reviewed in [12,13]] (fig. 1, right panel).…”
Section: Introduction: the Road From Biocompatibility To Bioactivitymentioning
confidence: 99%
“…The ultimate goal of using this vitamin was to increase the biocompatibility and to prevent the oxidative stress that is related to leukocyte oxidative burst, and other inflammation-related effects that may result from the interaction between blood constituents and cellulosic fibers [10]. More recently, in order to produce more biocompatible biomaterials, vitamin E has been coated on a polysulfone-based dialysis membrane [11], and this new vitamin E-coated polysulfone membrane has been demonstrated to have a redox capacity and to actively react with redox-active substances in the blood [12]. …”
Section: Introductionmentioning
confidence: 99%